TECHNOLOGICAL APPROACHES TO DESIGNING INTERACTIVE PRESENTATIONS FOR PROFESSIONAL TRAINING OF QUALIFIED WORKERS (Innovative professional education, 2023)
The experience of using interactive technology methods by teachers of professional training is presented. The urgency of developing digital literacy among future motor transport mechanics has been declared. The relevance of the use of information and communication technologies in the preparation of future specialists and qualified workers of road transport in the conditions of distance learning is analyzed.
Keywords: Webinar, distance learning, blended learning, information and communication technologies, SMART-complexes, professional competence, interactive presentation